Theoretical Study on the Effect of Triphenylamine on the Electronic, Optical and Charge Transport Properties of 2,1,3-Benzothiadiazole-Based Derivative - Hu, B.; Yao, C.; Jin, R.F. (Asian Journal of Chemistry, 2011)
A investigation of the variation in electronic, optical and charge transport properties upon the change of the molecular structure in 2,1,3-benzothiadiazole (BTD)-based derivative is presented using quantum-chemical approaches. Our quantum chemical calculations reveal that removing one triphenylamine unit in the backbone causes blue-shift in both the absorption and emission spectra relative to the pristine molecule. Such blue-shifts are attributed to the increase of the energy gap for the frontier molecular orbitals involved in the absorption and emission transitions. In addition, from the reorganization energy values based on charge hopping model, it is found that hole transportation is remarkably improved when removing one triphenylamine unit in the backbone, suggesting studied 2,1,3-benzothiadiazole-based derivative to be good hole transport material in organic light-emitting diodes.